2021
DOI: 10.1016/j.heliyon.2021.e08531
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax prevention practice and associated factors among farmers in Farta district, South Gondar, Amhara region, Northwest Ethiopia

Abstract: Background Anthrax is a zoonotic disease endemic in Ethiopia. Despite anthrax preventive measures are the key activities to control the disease, several outbreaks have occurred in Ethiopia recently. The objective of the study was therefore to assess the anthrax preventive practice and its associated factors among farmers in Farta district, South Gondar zone, Northwest Ethiopia. Method A community-based cross-sectional study was conducted among farmers in Farta District … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Although a third of pastoralists' knowledge was provided by animal health workers, only few public health workers (4.1%) contributed to community awareness. A similar lack of involvement of HEWs in disease knowledge transfer was observed in a study conducted in Gondar [15]. Our study showed that also the role of the media as a tool to raise disease awareness was very limited in these areas.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 85%
See 1 more Smart Citation
“…Although a third of pastoralists' knowledge was provided by animal health workers, only few public health workers (4.1%) contributed to community awareness. A similar lack of involvement of HEWs in disease knowledge transfer was observed in a study conducted in Gondar [15]. Our study showed that also the role of the media as a tool to raise disease awareness was very limited in these areas.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 85%
“…This raises the question whether Anthrax cases are highly under-reported in these pastoral areas. While sporadic outbreaks in both animals and humans are reported across the country [6,[14][15][16], to our PLOS NEGLECTED TROPICAL DISEASES knowledge, there are no peer-reviewed published reports specifically addressing Anthrax in Afar and SRS. However, in addition to our study, there have been regular reports of suspected Anthrax outbreaks documented in grey literature and local news sources.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Therefore, education is the cornerstone to expanding the knowledge of anthrax among the farmers' population and preventing its spread. These findings are supported by a study conducted in Ethiopia, in which education background and knowledge of anthrax were associated with better anthrax prevention practices (Mesfin et al, 2021). Other factors include sex (females had better anthrax prevention practice than males), time spent arriving at the nearby clinic, and attitude towards anthrax prevention (Mesfin et al, 2021).…”
Section: Tablementioning
confidence: 62%